A Prospective Study on inappropriate Drug utilization in Geriatric Patients at A Tertiary Care Teaching Hospital - Battula, Pradeep; Reddy, Thandlam Muneeswar; Prasad, Thammisetty Durga; Diviti, Ranganayakulu (Indian Journal of Pharmacy Practice)
Background: Prescribing to the older people is challenging. Pharmacokinetics and pharmacodynamic changes, chronic diseases, polypharmacy prescribing, potentially inappropriate medication (PIMs) prescribing, medication errors, adverse drug reactions, drug interactions, inappropriate prescribing or suboptimal prescribing are causes for challenge. It may lead to non-adherence, increase morbidity, length of hospitalization, poor quality of life, and finally death may occur. Method: A Prospective observational study was conducted in General Medicine department, for a period of 6 months. Patients of either gender who are above 65 years of age in general medicine in-patient ward with or without co-morbidities were included in the study; we excluded seriously ill and patients unable to communicate and Patients unwilling to participate in the study. Results: Total 140 geriatrics patients were admitted. In this study we observed that almost all prescriptions were with polypharmacy. PIMs observed from Beers criteria (17) and less in PRISCUS list (10). From both the lists 4 PIMs observed as same medications. Totally in 140 patients, 101 patients prescriptions were free from the PIMs, rest of the all potentially inappropriate prescriptions (PIPs). Conclusion: Inappropriate prescribing in geriatric patients is highly prevalent.
Keywords: Geriatrics; Potentially Inappropriate Medications; Beers list; PRISCUS list; NLEM list; WHO list